1984
DOI: 10.1128/aac.25.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Combined interferon-alpha 2, rimantadine hydrochloride, and ribavirin inhibition of influenza virus replication in vitro

Abstract: Recombinant DNA-produced human interferon-alpha 2 inhibited the replication of influenza A and B viruses in primary rhesus monkey kidney cells (RMK). Human interferon-alpha 2 interacted additively or synergistically with rimantadine hydrochloride or ribavirin in reducing the yield of clinical isolates of either H3N2 or H1N1 subtype influenza A viruses. The combination of human interferon-alpha 2 and ribavirin also inhibited the replication of an influenza B virus to a greater extent than either single agent. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…31 Reduction in adamantane resistance emergence in vitro by combination of rimantadine and ribavirin was reported in 1980, 32 a principle subsequently supported with amantadine and oseltamivir for many infl uenza A subtypes, including avian H5N1. 33 The fi rst triple infl uenza drug regimen (interferon alfa, rimantadine, and ribavirin) showing enhanced in-vitro activity against infl uenza A was described in 1984; 34 the investigators also noted enhanced activity with combinations of ribavirin and interferon alfa for an infl uenza B virus. Once neuraminidase inhibitors became available, preclinical studies showed additive or synergistic in-vitro activity and increased survival in murine models with combinations of an adamantane with a neuraminidase inhibitor.…”
Section: Historical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Reduction in adamantane resistance emergence in vitro by combination of rimantadine and ribavirin was reported in 1980, 32 a principle subsequently supported with amantadine and oseltamivir for many infl uenza A subtypes, including avian H5N1. 33 The fi rst triple infl uenza drug regimen (interferon alfa, rimantadine, and ribavirin) showing enhanced in-vitro activity against infl uenza A was described in 1984; 34 the investigators also noted enhanced activity with combinations of ribavirin and interferon alfa for an infl uenza B virus. Once neuraminidase inhibitors became available, preclinical studies showed additive or synergistic in-vitro activity and increased survival in murine models with combinations of an adamantane with a neuraminidase inhibitor.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…Interferon alfa shows enhanced anti-infl uenza activity in vitro with other antivirals, 29,34 in addition to its immunomodulatory properties. Some evidence shows that severely ill patients with infl uenza have defi cient endogenous interferon responses.…”
Section: Interferonsmentioning
confidence: 99%
“…Work in this field started over 40 years ago with an amantadine and interferon combination 74 . About 25 years ago, the first triple drug combination including interferon, rimantadine and ribavirin was described 75 . Subsequent pre‐clinical studies have indicated that if an influenza A virus is aminoadamantane‐susceptible, synergistic interactions in vitro and increased survival in murine models of influenza, including A(H5N1), are observed when the aminoadamantane is combined with a NAI or ribavirin 76–78 .…”
Section: Antivirals In Current Clinical Developmentmentioning
confidence: 99%
“…NAIs combined with adamantanes demonstrated additive or synergistic activity against adamantane-susceptible influenza viruses in vitro and in vivo, and decreased resistance development without evidence of cytotoxicity [32,40,[138][139][140][141][142]. Other drugs studied in combination with either NAIs or adamantanes include IFN-α, 2′-deoxy-2′-fluoroguanosine and ribavirin, which also demonstrated additive or synergistic effects in vitro and in mouse models, respectively [138,141,[143][144][145][146]. In a mouse model with amantadinesusceptible H5N1 virus, combination therapy with oseltamivir and amantadine showed increased survival rates and decreased viral replication in internal organs [9,140].…”
Section: Combination Therapymentioning
confidence: 99%